"Epistemology of the Closet": Narrative Seduction and the Power in the Belly in Kaizer Nyatsumba's "In Happiness and in Sorrow". Issue 3 (3rd July 2017) - Mkhize, Jabulani
Summary: In this article, the author explores how Kaizer Nyatsumba's short story, "In Happiness and in Sorrow, " deals with what Sedwick (2013) calls "the epistemology of the closet" by using interpellative strategies to dramatise narration as a seductive act (Chambers 1984). Starting from the premise that the power in the belly in Nyatsumba's story lies precisely in the fact that the narrative is told from the perspective of the abandoned wife, the author employs Ross Chambers' "renewed narratology" of studying "narrative situations in stories" to determine how Nyatsumba's narrative makes its "point" by using seductive narrative manoeuvres to win the ideological assent of its readers. For this reason, the bulk of the argument in this article has, as its central thrust, a discussion of the modalities of narrative seduction in Nyatsumba's narrative that can hold any reader's attention spellbound, regardless of how a reader responds to the issues it raises.